Analisa Pengaruh Parameter Proses Terhadap Uji Tarik Produk Hasil 3D Printing Berbahan Polylatic Acid - Gita Suryani Lubis; Muhammad Taufiqurrahman; Muhammad Ivanto (Jurnal Engine: Energi, Manufaktur, dan Material, 2021)
Fused Deposition Method (FDM) is one of the additive manufacturing methods or methods used by 3D printers. This FDM technology can produce models with a fairly good level of accuracy and strength. However, until now information about the magnitude of the value of accuracy, and the value of strength is very minimal. Because of this, it is necessary to do a test to determine the strength value of the specimens produced using 3D technology printing. The tests carried out aim to obtain settings optimal parameters on a 3D printer using PLA material which is measured by the magnitude of the tensile strength value of the resulting product. The test is carried out by measuring the amount of stress that occurs when the tensile test is carried out. The test was carried out using 81 samples that were printed using the parameters of infill print speed, fill density, extruder temperature, and layer height. Based on the test results, the highest stress value is 1.092 N/m2 with a combination of parameters infill print speed 60 mm/s, fill density 40%, extruder temperature 200oC, and layer height 0.1 mm. The results of the analysis show that the parameter extruder temperature has the greatest influence on the magnitude of the tensile test value, while the layer height parameter has the smallest effect on the value of the test specimen.